2020
DOI: 10.1021/acsanm.9b02067
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis Meets Spintronics; Spin Potentials Associated with Open-Shell Orbital Configurations Enhance the Activity of Pt3Co Nanostructures for Oxygen Reduction: A Density Functional Theory Study

Abstract: One of the main obstacles in the implementation of hydrogen fuel cells (HFC) lies in the efficiency loss due to the overpotential of the oxygen reduction reaction (ORR). Nowadays, the best catalysts for cathodes in HFC are Pt 3 Co nanostructures. The superior activity of these magnetic Pt-alloys, compared to metallic platinum, correlates with the milder chemisorption of the oxygenated intermediates on the surfaces of the alloy. Quantum spin exchange interactions (QSEI), including interlayer exchange coupling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 60 publications
(124 reference statements)
4
55
0
Order By: Relevance
“…Here, we would like to highlight the challenges and opportunities of spintronic oxygen electrocatalysis, which might provide some inspirations for the development of this field. Spin‐polarized DFT calculations with oriented spin ordering. Spin‐polarized DFT calculations are able to precisely reflect most of the thermodynamic feature of reactions on magnetic materials, and Gracia and co‐workers [ 17 ] have demonstrated that catalyst with different spin ordering exhibits different binding affinity to the reactants and intermediates of ORR. Thus, to accurately describe the spin‐related catalysis phenomena and provide more reliable predictions for catalyst design, spin‐polarized DFT calculations with oriented spin ordering should be employed.…”
Section: The Future Of Spintronic Oxygen Electrocatalysis: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we would like to highlight the challenges and opportunities of spintronic oxygen electrocatalysis, which might provide some inspirations for the development of this field. Spin‐polarized DFT calculations with oriented spin ordering. Spin‐polarized DFT calculations are able to precisely reflect most of the thermodynamic feature of reactions on magnetic materials, and Gracia and co‐workers [ 17 ] have demonstrated that catalyst with different spin ordering exhibits different binding affinity to the reactants and intermediates of ORR. Thus, to accurately describe the spin‐related catalysis phenomena and provide more reliable predictions for catalyst design, spin‐polarized DFT calculations with oriented spin ordering should be employed.…”
Section: The Future Of Spintronic Oxygen Electrocatalysis: Challengesmentioning
confidence: 99%
“…It has been demonstrated theoretically by Gracia and co‐workers that materials with dominating FM spin orderings generally exhibit better spin‐selected charge transport mobility. [ 17 ] The oxygen electrocatalysis could benefit significantly if materials dominated by FM spin orderings can be synthesized through simple and practicable processes. However, to date, one‐step synthesis of the commonly employed transition metal oxides (TMOs), such as perovskite and spinel oxides, with dominant FM ordering is technically difficult.…”
Section: The Future Of Spintronic Oxygen Electrocatalysis: Challengesmentioning
confidence: 99%
“…Magnetic catalysts are considered to be environmentally friendly as they can be easily and completely separated from reactants using an external magnet without any loss, unlike other heterogeneous catalysts requiring filtration, centrifugation and other techniques that might be quite sophisticated [70]. It is also known that not only charge transfer but also spin transfer may occur when the molecule is adsorbed on magnetic surface, enhancing its catalytic properties [71] and expanding the area of potential applications in spintronic devices [72]. Non-stoichiometric ones are presented both for the reference and as an intermediate step of thin films formation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 55,62–66 ] Meanwhile, ferromagnetic couplings in inorganic catalysts with magnetic ordering structure were demonstrated to selectively accumulate/remove appropriate e‐spins in the O 2 generation/conversion process (Figure 2b). [ 57,67–71 ] These pioneer works highlight the significance of spin‐related effect in oxygen electrocatalysis. [ 72–77 ]…”
Section: Introductionmentioning
confidence: 99%